An Oral Formulation of the Probiotic, Bacillus subtilis HU58, Was Safe and Well Tolerated in a Pilot Study of Patients with Hepatic Encephalopathy. (30th June 2020) - Yossef, Sayed; Clark, Frances; Bubeck, Sarah S.; Abernethy, John; Bayne, Thomas; Krishnan, Kiran; Young, Aicacia
Abstract : Background . Hepatic encephalopathy often results in high blood ammonia levels because of inefficient ammonia processing by the liver. Lactulose treatment promotes the growth of urease-producing gut bacteria and a reduced colon pH, thus reducing blood ammonia absorption. It is thought that probiotics as an add-on therapy may be beneficial. Patients and Methods . Bacillus subtilis HU58 was tested for safety and tolerability in patients with hepatic encephalopathy taking lactulose in this double-bind, placebo-controlled, 4-week pilot study. Study participants received one dose of B . subtilis HU58 or placebo (orally) for the first five days and two daily doses thereafter. Participants were monitored for safety and blood ammonia levels. Results . Forty patients participated (placebo, 11; probiotic, 29). Baseline characteristics were generally comparable; the mean baseline blood ammonia level was somewhat higher in the probiotic group. Mild or moderate treatment-emergent adverse events (TEAEs) were reported in 27.3% and 17.2% of patients in the placebo and probiotic groups, respectively; no severe TEAEs were reported. One patient (9.1%) taking placebo and two (6.9%) taking the probiotic experienced serious TEAEs (SAEs); none resulted in study discontinuation and all were considered to have no/unlikely relationship to the study product. There were no significant differences in the mean percent change (MPC) of blood ammonia levels between groups, though the probiotic group exhibited a trend toward a milder increase. Stratification of the probiotic group by baseline blood ammonia level (>60  μ g/dL and ≤60  μ g/dL) resulted in a significantly reduced MPC in the >60  μ g/dL subgroup (MPC (SD); ≤60  μ g/dL ( n  = 14), 35.3% (73.3); >60  μ g/dL ( n  = 14), −26.5% (24.4); p = 0.0087 ). Conclusions . Daily treatment with oral B . subtilis HU58 was safe and well tolerated over a 4-week period in patients with hepatic encephalopathy, and a significantly reduced MPC of blood ammonia level was observed in patients with a baseline level >60  µ g/dL.